PERANCANGAN MEDIA PROMOSI OBJEK WISATA KABUPATEN PADANG PARIAMAN - Sania Irmadiana; Zulhendra Zulhendra (Universitas Negeri Padang, 2019)
The research aims to design a media for tourism promotion of Padang Pariaman Regency with attractive appearance and user friendly to facilitate the dissemination of information and attracts tourists yo visit the attractions op Padang Pariaman regency. The media of tourism promotion in Padang Pariaman regency is designed by the waterfall method, using the Yii2 framework concept by applying the concept of model-view-controller (MVC). The results of this article are web-based tourism promotion in Padang Pariaman Regency so that information can be accessed anywhere. Information that can be accessed includes the latest travel news distributed by the Padang Pariaman District tourism office. And provides a photo gallery of attractions, so that tourists can see the natural charm and diversity of tourism in Padang Pariaman. In addition, the map feature is provided to make it easier for tourists to find the location of attractions and a testimonial feature that accommodates advice from tourists.Keywords: Tourist Attraction, Yii2 Framework, Padang Pariaman Regency.